Middle Meningeal Artery Embolization for Chronic Subdural Hematoma: A Multi-Center Experience of 154 Consecutive Embolizations. (18th November 2021) - Kan, Peter; Maragkos, Georgios A; Srivatsan, Aditya; Srinivasan, Visish; Johnson, Jeremiah; Burkhardt, Jan-Karl; Robinson, Timothy M; Salem, Mohamed M; Chen, Stephen; Riina, Howard A; Tanweer, Omar; Levy, Elad I; et al.
Graphical Abstract: